ANALYSIS OF THE INTERNAL CONTROL SYSTEM OF CASH RECEIVINGS AND DISTRIBUTIONS IN NON-PROFIT ORGANIZATIONS - Yulian Sahri; Anggrelia Afrida; Randi Hidayat (Jurnal Ekonomi, 2023)
This study discusses the Internal Control System in an educational non-profit organization, namely the Al-Manar Islamic Education Foundation (YPIA) Muhammadiyah Kepayang Lempuing Ogan Komering Ilir South Sumatra. The thing that is highlighted is the Internal Control System for Accounts Receivable for Education Development Contributions (SPP). This study took data from YPIA and analyzed it in a descriptive qualitative manner. The results of this study indicate that the implementation of the Internal Control System at YPIA has not been fully implemented in accordance with the applicable SOP (Standard Operating Procedures), this can be seen from the presence of arrears from student tuition fees.